2003
DOI: 10.1103/physreva.67.023613
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless and hydrodynamic excitations of trapped boson-fermion mixtures

Abstract: Within a scaling ansatz formalism plus Thomas-Fermi approximation, we investigate the collective excitations of a harmonically trapped boson-fermion mixture in the collisionless and hydrodynamic limit at low temperature. Both the monopole and quadrupole modes are considered in the presence of spherical as well as cylindrically symmetric traps. In the spherical traps, the frequency of monopole mode coincides in the collisionless and hydrodynamic regime, suggesting that it might be undamped in all collisional re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The calculated collective mode frequencies are shown to be in quantitative agreement with experiments [25,27,42]. The extension of the scaling theory to a coupled system was developed in the cases of degenerate Bose-Fermi mixtures [35,67].…”
Section: Scaling Theory For a Coupled Systemsupporting
confidence: 65%
See 2 more Smart Citations
“…The calculated collective mode frequencies are shown to be in quantitative agreement with experiments [25,27,42]. The extension of the scaling theory to a coupled system was developed in the cases of degenerate Bose-Fermi mixtures [35,67].…”
Section: Scaling Theory For a Coupled Systemsupporting
confidence: 65%
“…The scaling anzatz for the time-dependent density profiles for the Bose and Fermi superfluids are chosen as follows [35,67], respectively…”
Section: Scaling Theory For a Coupled Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of attractive interactions some analyses using semianalytical methods [26,27] have suggested that the lowest-lying monopolar mode should show a softening in the approach to collapse. A similar frequency softening is found for a pure condensate with increasingly large boson attractions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough stability consideration was made for the homogeneous case [28] but has not been generalized to trapped systems yet. Finally, the influence of finite temperature [29,30] and beyond mean-field effects [31][32][33][34] have also been investigated.…”
Section: The Richness Of Bose-fermi Mixturesmentioning
confidence: 99%